Indicators of daily blood pressure monitoring in patients with osteoarthritis with cardiovascular disorders in case of metabolic syndrome - Yarmukhamedova, Saodat Khabibovna; Gafforov, Xudoyor Xudoyberdiyevich (Science and Education, 2024)
The article presents the results of the use of combined laser therapy in patients with osteoarthritis with cardiovascular disorders in metabolic syndrome. The data of daily monitoring of blood pressure in 310 patients with osteoarthritis are presented. The patients of the main group received combined laser therapy according to the proposed method and traditional drug treatment.